CUSTOMER RELATIONSHIP MANAGEMENT IN PROMOTING A ROOM AT SHEO RESORT HOTEL BANDUNG - Nova Maulidian Hidayat (Jurnal Riset Bisnis dan Manajemen, 2021)
Service marketing by taking advantage of marketing communication can form a good relation with the consumer. This research aims to find out the program, process, communication media of Customer Relationship Management (CRM) implementation in promoting a room at Sheo Resort Hotel Bandung. The method used in this research is qualitative method with a case study approach based on symbolic interaction theory, and constructivist paradigm with key informants of hotel managers, marketing division and three customer informants of Sheo Resort Hotel Bandung. The result showed that the CRM program in promoting the room was by using continuity marketing, individual marketing (one to one marketing) and partner relation (partnering program) by providing and giving discount, voucher, special facility and membership card which include room discount. The CRM implementation needed a customer service and employee support at maximum, as well as program development to maintain customer’s loyality.